2020
DOI: 10.1093/ehjci/jeaa205
|View full text |Cite|
|
Sign up to set email alerts
|

New insights of tricuspid regurgitation: a large-scale prospective cohort study

Abstract: Aims To evaluate the burden of tricuspid regurgitation (TR) in a large cohort, determine the right ventricle involvement of patients with TR and determine the characteristics of isolated TR. Methods and results Prospective study where consecutive patients undergoing an echocardiographic study in 10 centres were included. All studies with significant TR (at least moderate) were selected. We considered that patients with one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 26 publications
1
31
0
2
Order By: Relevance
“…Finally, in both above-mentioned studies, the most frequent cause of TR was functional. The prevalence of functional TR over the organic (or primary) TR has been recently confirmed by Vieitez et al [ 9 ]. In their prospective study of patients with significant TR, the authors found that primary TR was present in 7.4% of patients, whereas functional TR was present in 92.6%.…”
Section: Introductionmentioning
confidence: 77%
“…Finally, in both above-mentioned studies, the most frequent cause of TR was functional. The prevalence of functional TR over the organic (or primary) TR has been recently confirmed by Vieitez et al [ 9 ]. In their prospective study of patients with significant TR, the authors found that primary TR was present in 7.4% of patients, whereas functional TR was present in 92.6%.…”
Section: Introductionmentioning
confidence: 77%
“… 1 , 2 , 3 , 4 , 5 Contemporary studies show that PPMs and implantable cardioverter-defibrillators (ICDs) can cause a nonnegligible rate of significant TR (greater than or equal to moderate) in up to 5% of overall cases, with an evident increase in heart failure hospitalization and mortality rates. 6 , 7 , 8 , 11 These devices can affect TV function by one or more mechanisms, including perforation or impingement of one or more leaflets, lead entanglement into the subvalvular apparatus, RV dyssynchrony, and cardiac device–related endocarditis with associated direct infectious damage to the valvular structure or leaflet flail/avulsion after lead extraction ( Table 1 ). While LPs theoretically avoid multiple of these potential device-mediated TR causes, the pacemaker interaction with the complex TV subvalvular apparatus remains.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac device–induced TR is common and is associated with incremental morbidity and mortality. 6 , 7 , 8 The primary interventional approach in these situations is lead extraction followed by alternative modalities of pacing, including the leadless pacemaker (LP) systems. Leadless pacemakers were shown to be a safe and effective alternative pacing mode, with a growing acceptance and utilization in the medical community.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the severity of TR by echocardiography remains challenging and controversial. Although the American Society of Echocardiography and the European Association of Cardiovascular Imaging guidelines considers three stages of FTR (mild, moderate, and severe) [28], the need has been felt for a more sensitive grading system [29]. A vena contracta ≥ 0.7 cm, effective regurgitant orifice area (EROA) of ≥0.40 cm 2 , and regurgitant volume ≥ 45 mL, qualify it as severe; however, no distinction is made after these particular parameters.…”
Section: Echocardiographymentioning
confidence: 99%
“…Thus, a more sensitive five-stage TR severity assessment (mild, moderate, severe, massive, and torrential) has recently been proposed aiming to further assist the optimal therapy choice [31]. Massive and torrential TR gradings may have implications regarding selecting of patients eligible for percutaneous treatment [29]. Nevertheless, this new grading system is not yet present in the guidelines of the main international societies.…”
Section: Echocardiographymentioning
confidence: 99%